PERANCANGAN INFORMASI KERIS BERUPA MULTIMEDIA INTERAKTIF BERBASIS KIOSK - Panindias, Asmoro Nurhadi (Acintya, 2009)
This art design study was inspired from Keris which is known as a World Heritage and received a honorary as a Masterpiece of The Oral and Intangible Heritage of Humanity from UNESCO. Recently the speed of enlarge information demand this nation to extend information about Keris to public. Multimedia interactive has been choosing, which is use computer function to create and join link and tool that possibly user to do a navigation, interaction, recreation and communication. More specific about multimedia interactive, this is designed with kiosk base. Kiosk is an information system base on computer that put in a place who can be access by public, offer access to information or transaction for a group of user constantly with various anonym, use a short time dialogue and user interface that typically simple.Keyword : Keris, Multimedia Interactive, Kiosk, Public Information